Regulatory issues [what is the QSR - Bartoo, G. (IEEE Engineering in medicine and biology magazine)
Mention good manufacturing practice (GMP) or quality system regulation (QSR) and many engineers will immediately think of mounds of questionably meaningless paperwork. Is that really what the QSR is about? Or is that impression brought about by bad implementations of the QSR and a lack of understanding as to why medical manufacturers need the QSR? This article gives more of an overview as to what the key ideas are behind the QSR.